Acute cardiac manifestations under immune checkpoint inhibitors—beware of the obvious: a case report. Issue 8 (12th August 2021) - Arangalage, Dimitri; Pavon, Anna Giulia; Özdemir, Berna C; Michielin, Olivier; Schwitter, Jurg; Monney, Pierre
Abstract: Background: Immune checkpoint inhibitors (ICI) have revolutionized the management of many cancer types by drastically improving the median survival rate of patients. However, this efficiency comes at the cost of a high rate of immune-related adverse events, including lethal cardiac manifestations. Rapidly fatal cases of ICI-induced myocarditis have been reported and drawn considerable attention over the past years. However, it is essential to bear in mind that not all cardiac events occurring under ICI therapy are necessarily myocarditis. Case summary: A 61-year-old female treated with pembrolizumab for a stage IV melanoma was admitted for chest pain leading to the diagnosis of ICI-related myocarditis based on the description of a discrete left ventricular subepicardial late gadolinium enhancement (LGE) on cardiac magnetic resonance (CMR) imaging. ICI were suspended and intravenous methylprednisolone initiated. A second line anti-MEK therapy was initiated. After a month of treatment, similar chest pain occurred. CMR revealed a midventricular stress cardiomyopathy and no LGE was detected. A posteriori interrogation revealed emotional stressors preceding both episodes. Review of the first CMR, performed 2 weeks after symptom onset, indicated a pattern compatible with the recovery phase of a stress cardiomyopathy and the presence of LGE was questioned. ICI were reintroduced without recurrence of cardiac events. Discussion: Not all cardiac manifestations occurring under ICI therapy are drug-related adverse events, therefore differential diagnoses must systematically be considered as the contraindication of ICI may have a major impact on patient prognosis. Cardiac imaging should be performed early and plays a key role in the management strategy.